Social Cognition in Kompas Daily Editorials - Zustiyantoro, Dhoni; Halim Ali, Abdul; Amali, Zakki (Centre for Literary and Cultural Studies, 2023)
This article discusses social cognition in the Kompas Daily editorial using Teun A van Dijk's theoretical framework. Social cognition, as the central concept in this theory, refers to how individuals process, store, and use social information in various forms of communication. This research explores how Kompas daily editorials utilize the principles of social cognition in forming public opinions and views. This study uses the content analysis method to analyze the Kompas daily editorial